Erysimum cheiri: The potential uterotonic medicinal herb - Ghazaleh Mosleh; Sasan Zaeri; Parmis Badr; Abdolali Mohagheghzadeh (Shiraz University of Medical Sciences, 2020)
Wallflower (Erysimum cheiri (L.) Crantz) belonging to the family Brassicaceae has been a well-known medicinal herb in Persian medicine. Several cardiotonic steroids have isolated from different parts of this plant. The intravaginal dosage forms of wallflower have been frequently used for uterotonic purposes in traditional medicine. Accordingly, the present study explores the most frequent indications of wallflower through the history, and suggests a pharmacologcal hypothesis about the intravaginal delivery of this cardiotonic steroide cintaining herb. In this regard, study was done by searching via electronic databases and search engines including Sciencdirect and Scopus, Medline/Pubmed, and Google Scholar. Information on traditional indications of the herb was extracted from the major traditional medicine manuscripts. As the result, the historical survey and the pharmacological evidences have supported the hypothesis that the inhibitory effects of wallflower cardiotonic steroids on the Na+ K+ATPase pumps of the myocytes could affect the local vasospasm resulting the hypoxia, ischemia and contraction of the uterine tissue. It is suggested that more experimental studies be directed on the efficacy and safety of cardiotonic steroids of wallflower to induce uterine contractility.